IMPLEMENTASI TEKNOLOGI RFID DALAM PERENCANAAN DAN PENGENDALIAN PERSEDIAAN BERBASIS ERP DI PT. RAJA BESI SEMARANG - Herwin Suprijono; Rindra Yusianto (JURNAL DIAN, 2011)
At manufacture companies, the problems in collecting data often comes from the product recording which depends on the entry of the data operator as a human error. Beside that, manuat checking is done to control the production by comparing the exist database then it will a probtem for the storing depaftment. The aim of this research is fo design the hardware and softare as a support for RFID. Designing this softare is for Decision Support Systemn (DSS) of company management in planning and controling the supply. Qualitative method is used in this research by applying the planning of the system through the steps of life cyle development system. Then the implementation concludes that RFID is a system needed in activity of reading data automatically which prevents the human error. Moreover, RFID is able to improve the product controlling system befter.lmplementation of the RFID and ERP technology can be used fo help the decision making inplanning and controlling production.Keywords : RFID, planning and controlling, supply, ERP, manufacture